2018
DOI: 10.1016/j.clbc.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

A European, Observational Study of Endocrine Therapy Administration in Patients With an Initial Diagnosis of Hormone Receptor-Positive Advanced Breast Cancer

Abstract: In this observational study we estimated the proportion of postmenopausal breast cancer patients initially diagnosed with hormone receptor (HR)-positive locally advanced or metastatic breast cancer (LA/MBC), using data from 6 European cancer registries (n [ 244,268 with known HR status and disease stage). Approximately 19,002 patients (7.8%) received an initial diagnosis of HR-positive LA/MBC; 74.5% (n [ 14,157) of these received subsequent endocrine therapy as per guideline recommendations. Background: Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
2
6
0
Order By: Relevance
“…The incidence of HR+/HER2− BC among all BC subtypes in our study was 64.8%, with 3.7% diagnosed as stage IV. These incidences are in line with those observed in a European registry analysis [23] and a US populationbased case-control study [24]. Interestingly, the proportion of patients with ER positive tumors was higher in our cohort than others (99% versus 86%) [23,24].…”
Section: Patient Characteristicssupporting
confidence: 92%
See 2 more Smart Citations
“…The incidence of HR+/HER2− BC among all BC subtypes in our study was 64.8%, with 3.7% diagnosed as stage IV. These incidences are in line with those observed in a European registry analysis [23] and a US populationbased case-control study [24]. Interestingly, the proportion of patients with ER positive tumors was higher in our cohort than others (99% versus 86%) [23,24].…”
Section: Patient Characteristicssupporting
confidence: 92%
“…These incidences are in line with those observed in a European registry analysis [23] and a US populationbased case-control study [24]. Interestingly, the proportion of patients with ER positive tumors was higher in our cohort than others (99% versus 86%) [23,24]. The majority of patients with stage I-III HR+/HER2− BC in our study had favorable prognostic features such as tumor size < 2 cm (53%), lymph node negative status (62%), and well to moderately differentiated tumor pathology (75%).…”
Section: Patient Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…In the UK, approximately 13–21% of patients with breast cancer receive a late-stage diagnosis (stage III or IV), and 6–7% of patients have metastases at diagnosis [2]; a large proportion of these patients are likely to be endocrine therapy-naïve. However, one European observational study found that approximately one-quarter of postmenopausal patients with an initial diagnosis of HR+ locally advanced or metastatic disease did not receive subsequent endocrine therapy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Most women diagnosed with oestrogen receptor positive (ER+ve) breast cancer in England are prescribed endocrine therapy (ET). ET decreases recurrence and increases survival [1] and is the current standard treatment for patients with ER+ve disease in both early and metastatic breast cancer [2]. Adherence to ET was reported to be between 40% and 70% over a five year treatment period [3,4].…”
Section: Introductionmentioning
confidence: 99%